Initial teacher education: What does it take to put equity at the center?. (July 2016) - Cochran-Smith, Marilyn; Ell, Fiona; Grudnoff, Lexie; Haigh, Mavis; Hill, Mary; Ludlow, Larry
Abstract: This article addresses the question: What would it take to put equity front and center in initial teacher education? Drawing on research and innovative programming, the authors argue there are four essential tasks: conceptualizing educational inequality and the role of teacher education in challenging inequality; defining practice for equity; creating curricula and structures that are equity-centered and tailored to local patterns of inequality; and, engaging in research for local improvement and theory building about the conditions that support candidates' equity practice. The article conceptualizes each of these tasks and illustrates how they have been addressed in one context. Highlights: Four tasks involved in making equity the centerpiece of initial teacher education. Task 1: Conceptualizing inequality/inequity and teacher education's role. Task 2: Defining practice for equity. Task 3: Creating equity-centered programs tailored to local history of inequality. Task 4: Researching equity-centered teacher education.